THE PORTRAYAL OF BLACK AMERICAN PEOPLE IN 1950âs THROUGH THE SETTING AND CHARACTER ANALYSIS IN WILSONâS FENCES - Sophia, Cicik (ETERNAL, 2010)
ABSTRACT The objective of this research is (1) to find out that the historical event that becomes the time set in âFencesâ compared to the real life; (2) to find out Troy Maxsonâs characteristics can be seen as the portrayal of Black American people who live in the same period as happened in âFencesâ. The method used in this research is qualitative by using historical approach. The outcome of this research are (1) The setting used in this drama are Â (a) historical setting; the drama takes place from the year 1950âs until 1960âs in America and (b) geographical setting; the drama takes place in Pittsburg, America; (2) Troy as the main character in âFencesâ has characteristics as (a) realistic man and when its compared to the life of black people in that era, it is still hard for the black people to achieve their dream such as the baseball player because he knows the condition at that time is hard for black people who want to be athletes; (b) uneducated, illiterate man and it is appropriate to the education condition in that era for blacks are segregated and very poor; (c) high tempered is as the consequence of the racial tension and discrimination toward blacks at that time. Â Keywords: setting, historical approach, characteristics, Black American people.